A comparison of species growth rates from four moist tropical forest regions using increment-size ordination. (1st September 2002) - Alder, D.; Oavika, F.; Sanchez, M.; Silva, J.N.M.; van der Hout, P.; Wright, H.L.
Growth rates and typical size are compared for 204 species from permanent sample plots in Brazil, Costa Rica, Guyana and Papua New Guinea. Growth rates were expressed as mean dbh increment, and typical size as 95% point of cumulative diameter distribution (D95). An ordination of species was analysed by a weighted cluster analysis method to form 16 species groups for the data from the 4 regions. Only trees 20 cm and above were included, and species with 50 or more sample trees. Results are tabulated for mean group increments, mortality rates and D95. Common species in each group and PSP locality are listed and their ecology discussed. Ecology and wood density are consistent between localities in their position on the increment-size graph. Mortality estimated by formula from the increment-size graph correlates with observed mortalities (R2 69.9%), although there is systematic overestimation. The methodology presented may be useful for estimating probable growth rates from forest inventory data where PSP data is lacking, for purposes of simple stand projection. A website (www.myrlin.org) provides worksheets, software and further documentation.